Reconceptualizing regional security in South Asia: A critical security approach. (October 2017) - Barthwal-Datta, Monika; Basu, Soumita
South Asia has garnered much attention in international security scholarship and policymaking, not least due to the number of protracted armed conflicts in the region. Yet, the dominant discourse on regional security in South Asia fails to adequately capture the insecurities that undermine the everyday lives and livelihoods of a majority of South Asians. The article first interrogates this prevalent discourse to reveal the inadequacies of traditional state-centric regional security analysis in South Asia. Drawing on critical approaches to security, including concepts that have been developed in the region, it then offers a reconceptualization of regional security. A brief case study discussion on food insecurity is employed to develop, and demonstrate the relevance of, such an approach to identifying and addressing contemporary security imperatives in South Asia. In doing so, the article presents a critical approach to regional security that is deeply rooted in South Asian experiences.